Science Learning Management Based on Higher Order Thinking Skills (HOTS) - Tina Rahmawati (Postgraduate, University of Mataram, 2023)
The purpose of this study was to describe Science Learning Management Based on Higher Order Thinking Skills (HOTS) in public high schools in Bantul Regency. This research is a quantitative research. The research locations were in 19 public high schools in Bantul Regency. This research was conducted from May to August 2019. The data source for this research was science teachers at public senior high schools in Bantul Regency. Data collection techniques using document studies. Data analysis techniques using quantitative data analysis techniques with percentages. The results showed that in terms of planning in public high schools in Bantul Regency, 82.5% were HOTS-based, but this percentage tended to decrease during the implementation of learning, namely 54.4% and about 58.3% in learning evaluation which should also HOTS based.